Long-term complications in kidney transplantation – 14 years of experience (Annals of Medical Research, 2025)
Aim: The increase in the number of kidney transplants and prolonged survival following kidney transplantation has increased the risk of posttransplant complications. The present study aims to investigate complications in kidney transplant recipients (eg, cardiac, hepatobiliary, opportunistic infections, avascular necrosis, NODAT) in our institution.Materials and Methods: A total of 300 patients who underwent renal transplantation in our institution have been evaluated in this retrospective analysis. The sociodemographic properties of age, sex, graft type, need for pre-transplant dialysis, and KFRT etiologies were obtained from hospital records. Avascular necrosis, malignancy, heart failure, or development of coronary arterial disorder, NODAT, opportunistic infections, and hepatobiliary complications have been evaluated.Results: The NODAT incidence in renal transplant patients was 17.5% in the case of living donor renal transplants versus 28.6% in cadaveric renal transplants (p=0.07). Again, 34% of the patients had hepatobiliary disorders such as cholelithiasis in the follow-ups, which was significantly higher in patients who received cadaveric transplants (p=0.009). Cytomegalovirus infection was observed in 50 patients, and BK virus infection in 36 patients. The rate of CMV infection was significantly higher in the first year after kidney transplantation. BK virus infections were found to be considerably higher in the first two years (p
Keywords: Renal transplant; Cholelithiasis; Opportunistic infection; New-onset diabetes after transplantation